2009
DOI: 10.1103/physreve.80.046218
|View full text |Cite
|
Sign up to set email alerts
|

Semiclassical description of wave packet revival

Abstract: We test the ability of semiclassical theory to describe quantitatively the revival of quantum wavepackets -a long time phenomena-in the one dimensional quartic oscillator (a Kerr type Hamiltonian). Two semiclassical theories are considered: time-dependent WKB and Van Vleck propagation. We show that both approaches describe with impressive accuracy the autocorrelation function and wavefunction up to times longer than the revival time. Moreover, in the Van Vleck approach, we can show analytically that the range … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 34 publications
0
19
0
Order By: Relevance
“…The Kerr system has been already investigated in depth [24,27,69,72], but its dynamics in phase space is worthwhile revisiting due to its fascinating geometry. We start by noticing that a classical phase space distribution under the action of the Kerr flow (65) will simultaneously revolve around the origin and be deformed into a filament, since outer points move faster than inner points.…”
Section: The Homogeneous Kerr Systemmentioning
confidence: 99%
See 2 more Smart Citations
“…The Kerr system has been already investigated in depth [24,27,69,72], but its dynamics in phase space is worthwhile revisiting due to its fascinating geometry. We start by noticing that a classical phase space distribution under the action of the Kerr flow (65) will simultaneously revolve around the origin and be deformed into a filament, since outer points move faster than inner points.…”
Section: The Homogeneous Kerr Systemmentioning
confidence: 99%
“…1 inspires pessimism with regard to a semiclassical approximation being able to reproduce quantum evolution, especially considering that its filamentary classical backbone gets thinner and thinner as time evolves (although its area obviously remains constant, by Liouville's theorem). This expectation was proven wrong in at least three occasions: In [72] it was was shown that a careful application of the vV-G propagator was successful in reproducing the evolved wave functions for more than one revival time; in [77] the H-K propagator was used to model a 0-dimensional Bose-Hubbard chain, for which the hamiltonian is given by the slightly different (yet dynamically identical) expression; and in [27] a value representation using final instead of initial values, proposed first in [64], was able to reproduce quantum dynamics with calculations performed directly in phase space. Since we know that these semiclassical analyses of the Kerr system were successful, we can be sure that semiclassical methods are supposed to work for this system.…”
Section: The Homogeneous Kerr Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple attempts to improve the TWA [19,33,34] suggest that more sophisticated methods [35][36][37][38][39][40][41][42][43] should be applied in order to describe the quantum evolution in terms of continuously distributed classical phase-space trajectories. Alternatively, different types of discrete phase-space sampling were proposed [44][45][46][47][48][49][50] in order to emulate evolution of average values using the main idea of the TWA.…”
Section: Introductionmentioning
confidence: 99%
“…There is no need for the classical Hamiltonian to be derived from a Lagrangian, so that the path integral may just as easily be constructed for e.g. the Kerr Hamiltonian [3,4,5], H(x) = (ap 2 + bq 2 ) 2 , as for the usual form, H(x) = p 2 /2m + V (q). A classical trajectory coincides with a stationary phase of the Weyl path integrand, just as with Feynman path integrals in the position representation.…”
Section: Introductionmentioning
confidence: 99%